The Problematic Learning in the New Normal Era at Students at SDN 03 Bandar Buat, Padang - Riswanti, Novia; Efendi, Nofriza; Antasya , Salma; Yuwandra, Ari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2023)
This study aims to analyze how the problems of learning in the new normal era for fourth grade students at SDN 03 Bandar for Padang City. This research uses qualitative research with problem analysis approach. The technique used by researchers in collecting data is a technique of observation, interviews, and documentation. The subjects of this research are fourth grade teachers and fourth grade students. This research was conducted at State Elementary School 03 Bandar Create Padang City in July 2022. The results of this study indicate that students tend to be bored and find it difficult to get material in online learning, and teachers find it difficult to provide understanding to students on material that is considered difficult. if not explained personally face to face. This is because students prefer to learn using the way the teacher explains in front of them.